Penyelesaian Wanprestasi Terhadap Kredit Logam Mulia(Studi di PT. Pegadaian Cabang Purwotomo Surakarta) - Wulandari, Sri, Septarina Budiwati, S.H., M.H (2016)
PT. Pegadaian is one of the financial institutions not affiliated with banks that offer credit financing of precious metals with the easy proviso that fits Pegadaian motto "Troubleshooting Without Problems". Prerequisite that are offered by PT. Pegadaian are customer has the KTP (Identity Card) and customer paid advances that have been determined by PT. Pegadaian. Furthermore, customers will receive a letter of agreement however precious metals such as gold is not accepted by the customer. Gold becomes the collateral deposited by the PT. Pegadaian. There are constrains on implementation of credit at PT. Pegadaian i.e make the customer can not pay installments until repayment. The constraint is that the customer makes a payment not on time, and the customer does not make payment at all. Liabilities that were not implemented these customers is a tort or break a promise that can lead to disputes that there must be a solution that is approved by the parties. Completion of each issue of agreement refers to the provisions of the Civil Code (KUHPerdata). In particular there is currently no law governing the credit however credit is generally equivalent to borrow money in accordance with the provisions of the Civil Code (KUHPerdata) Book III Chapter XIII of Lending and borrowing.